NGAL and NT-proBNP levels in diabetic patients with macroproteinuria. (21st August 2013) - Taskapan, Hulya; Taskapan, Mehmet Cagatay; Orman, Ibrahim; Ulutas, Ozkan; Yigit, Ali; Ozyalin, Fatma; Yologlu, Saim
Abstract: Background : In patients with heart failure plasma N-terminal pro-brain natriuretic peptide (NT-proBNP) levels are correlated to urine neutrophil gelatinase-associated lipocalin (NGAL) levels. We prospectively evaluated the relationship among glomerular filtration rate (eGFR), urine albumin-to-creatinine ratio (ACR), urine and serum NGAL and NT-proBNP levels in 20 type II diabetic patients with macroalbuminuria at 4-month intervals. Results : Compared with 20 age, gender-matched healthy controls, diabetic patients had higher urine and serum NGAL, serum NT-proBNP and lower eGFR. The eGFR of the patients at the baseline, the 4th and the 8th month were 29.6 ± 12.0, 27.8 ± 13.7 and 22.9 ± 10.4 mL/min/1.73 m 2, respectively. No significant change in urine NGAL levels was detected ( p > 0.05), whereas there were significant increases in NT-proBNP, serum NGAL and urine ACR and significant decrease in eGFR as the study progressed ( p < 0.05). Both the baseline and the 4th month urine ACR were positively correlated to NT-proBNP levels measured at the same periods ( r : 0.451; p : 0.046; r : 0.489; p : 0.029 respectively). In all measurements, urine ACR was negatively correlated to serum albumin levels measured at the same periods ( r : −0.792; p : 0.000; r : −0.716; p : 0.000; r : −0.531; p : 0.016 respectively). None of eGFR measurements was correlated with NT-proBNP ( p > 0.05). Neither serum NGAL nor urinary NGAL levels are associated with NT-proBNP ( p > 0.05). Conclusion : Our findings show an association between NT-proBNP and proteinuria in type II diabetic patients with macroalbuminuria but not with serum and urine NGAL.